THE ROLE OF CAFFEINE IN HEADACHE INDUCTION, TREATMENT AND PREVENTION - A LITERATURE REVIEW - Adrianna Świerzyńska,; Natalia Jankowska,; Natalia Pawelec,; Weronika Mazur,; Artur Hawajski,; Katarzyna Naja,; Tomasz Puszkiel, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Migraine is a chronic disorder with which caffeine has been associated for many years. It acts as both a trigger and an alleviating factor.  Caffeine consumption has a significant effect on the nervous system. Through its mechanism of action, it can trigger headaches, especially migraines. Both overuse and sudden withdrawal of caffeine can trigger migraine attacks, but can also be the cause of chronic migraine. People who suffer from migraines are advised to control their daily caffeine intake in order to avoid the symptoms associated with caffeine consumption. Caffeine has positive effects, boosting cognitive function, alertness, physical performance and endurance. Through its neuroprotective effects, it reduces the risk of Alzheimer's disease and Parkinson's disease.Aim of the study: The aim of this review is to summarise the existing knowledge on the effects of caffeine as an inducer of migraine headache, non-migraine headache, its role in withdrawal syndrome and its potential use in the treatment of various forms of headache.Material and methods: Our research method involved searching publicly accessible online databases of academic articles, such as PubMed, Google Scholar, and others. The research team used the keyword “migraine” in combination with various terms, including “caffeine consumption”, “treatment”, “prevention”, “caffeine intake” and “caffeine withdrawal”. The collected data were then manually analyzed.Results and Conclusions: Caffeine has a dual role in migraine, acting both as a potential trigger and as an effective adjunct in treatment. Its impact on adenosine receptors explains both analgesic and pain-inducing effects. Controlled use can support acute migraine therapy, especially with analgesics, while awareness of withdrawal risks and individual tolerance is crucial to precluding headaches.